'Wit's Wild Dancing Light' Reading the Poems of Alexander Pope - Hutchings, William (Open Book Publishers, 2023)
The book is a chronological reading of Alexander Pope's poems, from the Pastorals (1709) to the four-book Dunciad (1743). Each of the 26 chapters forming the volume selects examples for detailed scrutiny, demonstrating how close reading can generate understanding of a whole poem and how critical appraisal can build into a creative survey of an entire poetic career. The book's approach is intended to be both scholarly and accessible and 'Wit's Wild Dancing Light' will be of interest to scholars, students and anybody interested in Pope's masterful poetry.